Cultivar and Training System Impact Cold-climate Seedless Table Grape Performance in the Northeastern United States - Rebecca Grube Sideman; George Hamilton; Kaitlyn Orde (HortScience)
We grew eight cultivars of seedless table grape in Durham, NH, USA, from 2015 to 2021, using two training systems: Munson and vertical shoot positioning (VSP). We evaluated the vine vigor, prevalence of common diseases, yield, and postharvest fruit weight loss. We observed that cultivar significantly impacted vine vigor and the prevalence of three common diseases. One year after planting, the cultivars Thomcord, Marquis, and Lakemont had significantly less vigor than that of other cultivars, and Thomcord and Marquis both exhibited high mortality (38% and 29%, respectively). ‘Marquis’ and ‘Thomcord’ consistently showed among the highest prevalence of most diseases present in the vineyard (powdery mildew, anthracnose, and downy mildew), whereas ‘Concord Seedless’, ‘Canadice’, and ‘Mars’ consistently showed among the fewest symptoms. ‘Thomcord’ and ‘Marquis’ were removed from the experiment in 2019. For the six remaining cultivars, the cultivar, year, training system, and all interaction terms significantly affected yield. ‘Mars’ produced the highest yield throughout the study, reaching a maximum yield of over 15 kg/vine in their seventh season in the vineyard. Overall, yields of vines growing on the Munson training system were greater than those growing on the VSP system (P < 0.0001), although the advantages of growing on Munson were greater for some cultivars than for others (e.g., the yield advantages in 2021 were only 8% for ‘Lakemont’ but reached 90% for ‘Concord Seedless’ and 74.8% for ‘Vanessa’). ‘Mars’ exhibited the lowest percentage weight loss after 28 days of cold storage, which was significantly lower than that of all cultivars except Reliance. In conclusion, ‘Mars’, ‘Canadice’, ‘Vanessa’, and ‘Lakemont’ offer potential for commercial production of seedless table grapes in the northeastern United States based on producing moderate to high yields of consistently high-quality fruit; of these, ‘Mars’ showed the least susceptibility to common diseases and postharvest weight loss.